2019
DOI: 10.1002/jcb.28373
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MIR503HG functioned as a tumor suppressor and inhibited cell proliferation, metastasis and epithelial‐mesenchymal transition in bladder cancer

Abstract: Bladder cancer is the most common malignancy with high recurrence. Currently, the long noncoding RNAs (lncRNAs) have been suggested to play vital roles in the pathogenesis of bladder cancer. The present study investigated the role of lncRNA MIR503 host gene (MIR503HG) in the pathogenesis of bladder cancer by using both in vitro and in vivo functional assays. The expression of MIR503HG was downregulated in bladder cancer tissues and cell lines. Low expression of MIR503HG was associated with advanced tumor stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…In bladder cancer, miR503HG was also downregulated and suppressed cancer progression by inhibiting cancer cell proliferation and invasion. 17 Similarly, we also Figure 2 Cisplatin treatment further downregulated miR503HG in both patients and CSCC cells. Expression levels of miR503HG in plasma collected from CSCC patients at 0, 3, 6 and 9 weeks after the initiation of cisplatin treatment were measured by qPCR.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In bladder cancer, miR503HG was also downregulated and suppressed cancer progression by inhibiting cancer cell proliferation and invasion. 17 Similarly, we also Figure 2 Cisplatin treatment further downregulated miR503HG in both patients and CSCC cells. Expression levels of miR503HG in plasma collected from CSCC patients at 0, 3, 6 and 9 weeks after the initiation of cisplatin treatment were measured by qPCR.…”
Section: Discussionsupporting
confidence: 62%
“…15 LncRNA MIR503 Host Gene (miR503HG) has been reported to be a tumor suppressor in several types of cancers. 16,17 However, its exact functioning role in cervical cancer is unclear. By analyzing the TCGA dataset, we found that miR503HG was significantly downregulated in cervical squamous cell carcinoma (CSCC), which is a major subtype of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA PEG10 interacted with miR‐29b to enhance BC cell proliferation, migration and invasion . In addition, Qiu et al demonstrated that lncRNA MIR503HG acted as a tumor suppressor, which inhibited cell proliferation, metastasis and epithelial‐mesenchymal transition process in BC . It was described that MBNL1‐AS1 was a novel lncRNA to potentially predict the prognosis of gastric cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al suggested that MIR503HG exhibited significant antiproliferation, antimigration/invasion effects on bladder cancer cells [31]. Chou et al demonstrated that MIR503HG overexpression inhibits colorectal cancer (CRC) cell migration and invasion mediated by TGF-β2 [32].…”
Section: Accepted Articlementioning
confidence: 99%